Epidemiological characteristics, clinical manifestations, and mental health status of human mpox cases: A multicenter cross‐sectional study in China - Fu, Leiwen; Wang, Bingyi; Wu, Ke; Yang, Liuqing; Hong, Zhongsi; Wang, Ziyu; Meng, Xiaojun; Ma, Ping; Qi, Xiao; Xu, Guangyong; Wang, Fuxiang; Zhang, Weijie; et al. (Journal of medical virology, 2023)
Human mpox is occurring worldwide, however, evidence from the Asian Pacific Region is limited. In this multicenter cross‐sectional study, information of confirmed mpox cases diagnosed between June 1 and July 31, 2023 in China. Information included demographic and epidemiological characteristics, and clinical manifestations, laboratory results, and mental health status of mpox cases. A total of 115 confirmed mpox cases were enrolled. All cases were men. A total of 102 (90.3%) identified as homosexual. The median age was 31.0 years (interquartile range 27.0–36.5). A total of 65 (56.5%) were HIV‐positive, of whom 92.3% were receiving antiretroviral therapy (ART). A total of 19/39 (40.4%) had a CD4 cell count <500 cells/μL. Systemic features such as fever (73.0%), lymphadenopathies (49.6%), and myalgia (28.7%) were commonly observed. Skin lesions were present in all participants: 49.6% in the genital area and 27.0% in the perianal area. Vesicular rash (78.3%) and papular rash (44.3%) were the most common lesion morphologies. People living with HIV were more likely to have anxiety than those living without HIV. The majority of mpox cases had primary genital lesions and sexual activities before diagnosis, which supports the likelihood of sexual contact transmission. Guidelines on hospitalization and isolation protocols for mpox patients necessitate further confirmation.